Landscape of adenosine pathway and immune checkpoint dual blockade in NSCLC: progress in basic research and clinical application - Wang, Rulan; Liu, Zhenkun; Wang, Ting; Zhang, Jiabi; Liu, Jiewei; Zhou, Qinghua (Frontiers in Immunology, 2024)
Lung cancer poses a global threat to human health, while common cancer treatments (chemotherapy and targeted therapies) have limited efficacy. Immunotherapy offers hope of sustained remission for many patients with lung cancer, but a significant proportion of patients fail to respond to treatment owing to immune resistance. There is extensive evidence to suggest the immunosuppressive microenvironment as the cause of this treatment failure. Numerous studies have suggested that the adenosine (ADO) pathway plays an important role in the formation of an immunosuppressive microenvironment and may be a key factor in the development of immune resistance in EGFR-mutant cell lung cancer. Inhibition of this pathway may therefore be a potential target to achieve effective reversal of ADO pathway-mediated immune resistance. Recently, an increasing number of clinical trials have begun to address the broad prospects of using the ADO pathway as an immunotherapeutic strategy. However, few researchers have summarized the theoretical basis and clinical rationale of the ADO pathway and immune checkpoint dual blockade in a systematic and detailed manner, particularly in lung cancer. As such, a timely review of the potential value of the ADO pathway in combination with immunotherapy strategies for lung cancer is warranted. This comprehensive review first describes the role of ADO in the formation of a lung tumor-induced immunosuppressive microenvironment, discusses the key mechanisms of ADO inhibitors in reversing lung immunosuppression, and highlights recent evidence from preclinical and clinical studies of ADO inhibitors combined with immune checkpoint blockers to improve the lung cancer immunosuppressive microenvironment.